FAITH IN THE MARKETPLACE: HOW AMANAH SHAPES SOCIAL TRUST AND CONSUMER LOYALTY AMONG MUSLIM SMES IN INDONESIA - Besse Faradiba; Ida Ilmiah Mursidin; Damirah; Aulia Nur Irsha (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the sociological role of Amanah (trustworthiness) as a spiritual-social foundation in Islamic SMEs and how it bridges the gap between formal management strategies, product quality, and consumer loyalty. It specifically investigates the potential paradox where religious ethics might interact unpredictably with modern management practices. A quantitative approach was employed utilizing Partial Least Squares-Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0. Data were gathered via a structured survey involving 313 respondents, comprising active consumers and business practitioners of Islamic SMEs in Makassar, Indonesia. The results reveal that while management strategy and product quality significantly and positively influence loyalty, a striking paradox emerges: Amanah shows a significant negative moderation effect on the relationship between management strategy and consumer loyalty. This suggests that over-reliance on formal management may diminish the organic trust-building power of religious ethics. However, Amanah remains a full mediator that converts product quality into long-term loyalty. The findings suggest that "success" in Islamic business is not a simple linear integration of modern and traditional values. While formal management is essential, the traditional-religious value of Amanah constitutes a distinct form of social capital that can be stifled by excessive formalization. Practitioners must balance professional systems with authentic spiritual integrity to stabilize market relations. This study contributes to Islamic economic literature by empirically uncovering the "tension" between religious integrity and formal business strategy. It offers a new integrative framework that challenges the assumption that religious ethics and modern management always work in perfect harmony.